Pengaruh Intellectual Capital, Perputaran Modal Kerja, dan Biaya Operasional Pendapatan Operasional Terhadap Profitabilitas - Yustikasari, Devi Riski; Amalia Arifah, Dista (Economic Reviews Journal, 2025)
This study aims to examine whether there is an influence of intellectual capital, working capital turn over, and operating expenses operating income on profitability. The research population comprises health sector companies listed on the Bursa Efek Indonesia (BEI) during 2021–2024. A total of 23 companies were selected as the sample using purposive sampling, a non-probability sampling technique. Multiple linear regression analysis was conducted using SPSS version 27. The results of this study indicate that intellectual capital has a positive and significant influence on profitability, working capital turnover has no influence on profitability, and the operating expense to operating income ratio has a negative and significant influence on profitability.